The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1ta07856a
|View full text |Cite
|
Sign up to set email alerts
|

Research progress in metal–organic frameworks (MOFs) in CO2capture from post-combustion coal-fired flue gas: characteristics, preparation, modification and applications

Abstract: In response to the urgency of reducing CO2 emissions, nearly 200 countries have joined the "Paris Agreement". It sets long-term low-carbon development goals, which aim to achieve carbon neutrality in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 174 publications
(202 reference statements)
0
22
0
Order By: Relevance
“…This method is beneficial to the crystallization of insoluble substances and the synthesis of large size single crystal. [64] For instance, Huang et al [65] firstly put the methanol solution of ligand on top of the ammonia solution of Zn(OH) 2 by diffusion method, and obtained the largesize ZIF8 crystal after several days. At present, it has been reported that this method was also used to prepare ZIF8 nanoparticles with uniform morphology.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…This method is beneficial to the crystallization of insoluble substances and the synthesis of large size single crystal. [64] For instance, Huang et al [65] firstly put the methanol solution of ligand on top of the ammonia solution of Zn(OH) 2 by diffusion method, and obtained the largesize ZIF8 crystal after several days. At present, it has been reported that this method was also used to prepare ZIF8 nanoparticles with uniform morphology.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…At present, carbon capture, utilization, and storage (CCUS) technology is the most ideal technology to realize large-scale low-carbon emissions of fossil energy . Considering the defects of high energy consumption and high viscosity of traditional industrialized organic amine aqueous solutions, the development of efficient CO 2 adsorbents has become a key problem to be solved urgently in this research field …”
Section: Introductionmentioning
confidence: 99%
“…The rapid consumption of fossil fuels has caused the continuous increase in carbon dioxide (CO 2 ), which leads to global warming and serious environmental problems. 1,2 Therefore, how to control the continuous increase of CO 2 levels in the atmosphere has become a worldwide problem needing urgent resolution. 3,4 Meanwhile, CO 2 is an inexhaustible, cheap, and nontoxic C1 resource.…”
Section: Introductionmentioning
confidence: 99%